Penerapan Pengakuan Pendapatan dan Biaya pada Perusahaan Kontruksi - Bambang Eka Dwi Cahyono; MOH Halim; Rendy Mirwan Aspirandi (BUDGETING : Journal of Business, Management and Accounting, 2022)
This study aims to determine the application of PSAK No. 34 to the revenue recognition method used by CV Wahid Jaya Abadi. This research method is descriptive. Data collection techniques used are interviews, observation, and interviews. The results showed that some of the projects carried out by CV Wahid Jaya Abadi had less than one accounting period (short term) and some had more than one year of accounting period (long term). The project that is the case study is a project that has a one-year accounting period (March 2018-February 2019) with a contract worth Rp.860.000.000-. The revenue recognition method used is the completed contract method and the presentation of revenue recognition using a cash basis. In conclusion, the revenue recognition method used by CV Wahid Jaya Abadi is still not in accordance with PSAK No. 34. This is because this company has not used the percentage method for long-term projects. Keywords: Cash Basis, Completed Contract, PSAK No. 34